USE OF TEMPORARY ANCHORAGE DEVICES IN INTRUSION OF SUPRAERUPTED MOLARS-CASE REPORTS - Trpevska, Vesna; Tanatarec, Ivan; Shushak, Zoran; Srbinoska, Daniela; Stavreva, Natasha (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Early loss of mandibular permanent molars with supraeruption of maxillary permanent molars is a common clinical finding causing functional posterior occlusion problems. Rehabilitation of the stomatognathic system often requires preprosthodontic intervention with molar intrusion which is one of the most difficult movements in orthodontic mechanics requiring efficient anchorage to achieve success. The aim of this article was to present two case reports, with orthodontic mini-implants used for molar intrusion as preprosthetic treatment, reducing the need for prosthetic crown reduction in patients with edentulous space discrepancy. With the aid of chain elastics, the force of intrusion passing through the center of resistance of the tooth, supraerupted maxillary molars were intruded approximately 0.5mm per month. The intrusive tooth movement maintained the vitality of the intruded teeth and was not aggressive to the periodontal structures, did not cause root resorption and no change of the pulp flow was detected. In contrast to traditional orthodontics, mini-implants were demonstrated to be clinically efficient in providing sufficient anchorage against orthodontic forces. With these devices using well-controlled magnitude and direction of the force, we reestablished successfully the functional posterior occlusion. Through this case reports, we emphasize the versatility of orthodontic mini-implants as a form of temporary anchorage devices (TADs) in the biomechanics of molar intrusion attempted to create interocclusal space for adequate prosthodontic restoration with osseointegrated implants and prosthesis. Keywords: Temporary anchorage devices (TADs), Mini-implants, Molar intrusion, Edentulous space discrepancy, Preprosthodontic therapy.